2001
DOI: 10.1143/jjap.40.6868
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Holographic Grating based on Dye-Doped Polymer-Ball-Type Polymer-Dispersed Liquid Crystal Films

Abstract: This study investigates the characteristics of the holographic grating formed in polymer-ball-type polymer-dispersed-liquid crystal (PBT-PDLC) films, doped with a diazo dye (G206). A dye-doped PBT-PDLC sample was fabricated, and used to write a holographic grating. Experimental results indicated that the grating had memory of the polarization of the writing beams. This polarization memory effect was inerasable if the sample was heated to the isotropic phase, and then cooled down to room temperature. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The resultsthat both the zeroth-and first-order diffraction efficiencies of the s-polarized pumped grating change periodically with the angle -are believed to be caused by the adsorbed dyes in the high-intensity regions of the interference pattern that is set up by the two writing beams. 14,15 Briefly, the photo-excited dyes in these regions diffused and then adsorbed in a direction perpendicular to the polarization and the propagation directions of the pump beam ͑s-polarized͒. The adsorbed dyes then reoriented LC molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The resultsthat both the zeroth-and first-order diffraction efficiencies of the s-polarized pumped grating change periodically with the angle -are believed to be caused by the adsorbed dyes in the high-intensity regions of the interference pattern that is set up by the two writing beams. 14,15 Briefly, the photo-excited dyes in these regions diffused and then adsorbed in a direction perpendicular to the polarization and the propagation directions of the pump beam ͑s-polarized͒. The adsorbed dyes then reoriented LC molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Adding a small amount of azo dye into the PDLC materials, polarization sensitive gratings can be obtained by holography [28]. The formation of the polarization gratings is attributed to the anisotropic adsorption of the azo dyes on the surfaces of polymer walls, inducing the reorientation of the liquid crystal molecules [29]. Figure 7 shows a sharp grating contrast under an optical microscope with a polarizer parallel and perpendicular to the direction of the stripe in the grating, respectively.…”
Section: Azo Dye Doped H-pdlcmentioning
confidence: 99%
“…Grating images observed under an optical microscope with a polarizer placed in front of the sample. The transmission axis of the polarizer is (a) parallel and (b) perpendicular to the direction of the stripes in the grating[29].…”
mentioning
confidence: 99%
“…Recently, it has been also reported that the memory effect occurs on the polymer wall of a dye-doped polymer-dispersed liquid crystal (PDLC) [8]. The alignment of the doped PDLC with azo-dyes was found to be stable without appreciable relaxation due to surface interactions between the LC and the dye molecules at the LC droplets dispersed in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%